1984
DOI: 10.1161/01.str.15.2.366
|View full text |Cite
|
Sign up to set email alerts
|

The isolated occlusion of the angular gyri artery. A correlative neurological and anatomical study--case report.

Abstract: We examined a patient who had signs of a cerebral hemisphere lesion: right hemiparesis, facial weakness, right hemianopsy, acustico-mnestic dysphasia, "empty speech," acalculia, visuo-spatial agnosia and constructional apraxia, but without changes in consciousness. Taking into account clinical signs, computed tomography and carotid angiography findings, we concluded that our patient had an infarction zone in the left temporo-parieto-occipital region, as a consequence of the isolated angular gyri artery (ANG) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Branches of the MCA (anterior and/or posterior parietal arteries or the angular artery) supply regions within the ‘traditional’ posterior external borderzone. It is possible that occlusion of these vessels gives rise to infarcts which are thought to be borderzone infarcts [34,35,36]. The anterior parietal artery supplies the antero-superior part of the post-central gyrus and the superior parietal lobule [35, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branches of the MCA (anterior and/or posterior parietal arteries or the angular artery) supply regions within the ‘traditional’ posterior external borderzone. It is possible that occlusion of these vessels gives rise to infarcts which are thought to be borderzone infarcts [34,35,36]. The anterior parietal artery supplies the antero-superior part of the post-central gyrus and the superior parietal lobule [35, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The posterior parietal artery supplies the supramarginal gyrus and postero-superior part of the parietal lobe [35, 37]. The angular artery supplies the angular gyrus and the caudal part of the superior and middle temporal gyri [35,36,37,38]. The temporo-occipital artery supplies the posterior half of the superior temporal gyrus, the posterior part of the middle and inferior temporal gyri, and the inferior parts of the lateral occipital gyri.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the division into two final branches, superior branch ends in intraparietal sulcus (25%), transverse occipital sulcus (30%), superior and inferior temporal gyrus (40%) or inferior temporal gyrus (5%); inferior branch ends in lunate sulcus (25%), superior temporal gyrus (5%) or middle and inferior temporal gyrus (70%). [13] Ring, B. A. study showed that inferior branch of AGA ended 1 to 3 centimetres away from occipital pole dorsally in 42% of 34 telencephalons.…”
Section: Resultsmentioning
confidence: 96%
“…[12] In least common cases, AGA has the same diameter as the temporooccipital and the posterior parietal artery, and rarely, a smaller diameter than aforementioned vessels. [13] Generally, AGA appears as a singular branch (88%), seldom as two separate branches (12%) of MCA. Near the angular gyrus or directly below, AGA often (63%) divides into two final branches: superior and inferior; less often (21%) into three or four final branches or no branches at all (16%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation